Contamination-resistant multifunctional coatings - Felde, Nadja; Munser, Anne Sophie; Gärtner, Anne; Schröder, Sven; Tünnermann, Andreas (Optics InfoBase Conference Papers, 2019)
Combining thin film design with structural design enables contamination-resistant coatings with high optical quality to be realized. Balancing self-cleaning and light scattering relevant structural components is of particular importance.
CRIS-Team Scopus Importer:2023-04-20